The Mechanisms Design and Stress Analysis of Convertible Booster Seat - Nek Man, Mohamad FIkrie; Mohamed, Norirda; mahmudin, rahmah (Progress in Engineering Application and Technology, 2021)
Transportation is one of the significant things today as it has a positive economic and social impact. However, most of the car seats available on the market are created not to prevent whiplash, especially to smaller passengers. Therefore, the objectives of this study are to design convertible middle rear seat using the morphological chart and to analyze the strength of a convertible booster seat mechanism. Solidworks 2018 is used to design the mechanism of the convertible booster seat. Characteristics that being studied to perform a better convertible booster is the mechanism, the joining method and the material used for the mechanism. Solidworks simulation 2018 are chosen to analyze stress concentration, displacement and strain of the convertible booster seat. For the simulation, all the mechanisms are tested with different loads, of 20 kg, 40 kg, 60 kg and 80 kg. Graph of stress analysis, displacement and deformation of the mechanism were recorded and analyzed. The success of this study will able the researcher and manufacturer to implemented the convertible booster seat for the safety of passengers especially kids and dwarf that use the middle rear seat.